2013
DOI: 10.1007/s00402-013-1755-0
|View full text |Cite
|
Sign up to set email alerts
|

A multi-level rapid prototyping drill guide template reduces the perforation risk of pedicle screw placement in the lumbar and sacral spine

Abstract: The method significantly lowers the incidence of cortex perforation and is therefore potentially applicable in clinical practice, especially in some selected cases. The applied method, however, carries a potential for errors during manufacturing and practical usage and therefore still requires further improvements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(63 citation statements)
references
References 15 publications
2
52
0
9
Order By: Relevance
“…Patient-specific instrument (PSI) has been reported as an alternative intraoperative assistance to computer navigation. PSI is applied to joint arthroplasty, [8,9] spinal pedicle screws insertion [10,11] and deformity correction. [12,13] PSI has recently been investigated in bone tumor surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Patient-specific instrument (PSI) has been reported as an alternative intraoperative assistance to computer navigation. PSI is applied to joint arthroplasty, [8,9] spinal pedicle screws insertion [10,11] and deformity correction. [12,13] PSI has recently been investigated in bone tumor surgery.…”
Section: Introductionmentioning
confidence: 99%
“…RP technology is widely used in the field of orthopedics, and may quickly transform digital design into a physical entity. In recent times, a number of spinal screw guides have been produced using RP technology [10][11][12]. However, to our knowledge and understanding, only a few have achieved desired effects.…”
Section: Discussionmentioning
confidence: 99%
“…However, to our knowledge and understanding, only a few have achieved desired effects. It has been reported that 26% of all pedicle screws were inserted inaccurately, with the length of 14% of screws too dissimilar in design for successful use of the multi segmental lumbosacral screw guide designed by Merc [10]. In this study, we used RP technology to make our own TFS guide.…”
Section: Discussionmentioning
confidence: 99%
“…For example, zygoma implants are used for functional reconstruction of maxillary defects [4], iliosacral screw insertions are utilized for treating pelvic fractures [5], and pedicle screw placement is adopted for spine surgery [6]. However, intraoperative drilling performance still poses a significant challenge for surgeon due to anatomic intricacies in the surgical region.…”
Section: Introductionmentioning
confidence: 99%